The basis for loan default repayments in microfinance institutions (MFIS) in Ghana: a case of microfinance institutions in Kumasi metropolis. - Adjei, Raphael Turkson (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment Of The Requirement For The Award Of The Degree Of Master Of Science In Economics.